Activation of the Large-Conductance, Voltage, and Ca2+- Activated K+ (BK) Channel in Acute Spinal Cord Injury in the Wistar Rat Is Neuroprotective - Jacobsen, Marianne; Lett, Kristen; Barden, John Mark; Simpson, Gavin L.; Buttigieg, Josef (Frontiers in Neurology, 2018)
Context/Objectives: Spinal cord injury (SCI) results in significant neuronal and glial cell death resulting in impaired neurological and motor function. Uncontrolled Ca2+ entry results in excitotoxicity and cell death. In this study, we examine the use of a BK channel activator, Isopimaric acid (ISO), as a neuroprotective agent post SCI as this channel is involved in regulating Ca2+ entry. Design: By using a 25-g clip compression at the T6 level, we generated a SCI event in wistar rats. At 1 hour post injury we administered ISO (BK channel activator), the BK channel inhibitor iberiotoxin (IbTx), or a vehicle control for 4 weeks via mini osmotic pump (pump capacity). For 8 weeks post injury, gait analysis of motor function was performed. At the end of 8 weeks, the extent of myelination in the spinal cord was assessed in addition to the electrophysiological profile. Results: Our immunohistological data suggests that ISO treatment leads to an increase or preservation of myelinated axonal tracts. This was further supported by our electrophysiological studies which demonstrate higher compound action potential amplitudes and speed of transmission in ISO-treated animals compared to inj-non-treated. Finally, treatment with ISO significantly improved motor function in our test model. Conclusion: In conclusion, activation of the BK channel during acute SCI may be a novel therapeutic target for acute SCI. Key words: Spinal cord injury, excitotoxicity, motor function, electrophysiology